Renewable banana-peel-derived activated carbon as an inexpensive and efficient electrode material showing fascinating supercapacitive performance. Issue 6 (December 2021) - Tripathy, Alekhika; Mohanty, Smita; Nayak, Sanjay Kumar; Ramadoss, Ananthakumar
Abstract: Activated carbon (AC) was synthesized from banana peel by treatment of the dried, and powdered peel using a one-step chemical activation process with an aim of improving the electrochemical performance of the electrodes fabricated using this AC. Here we investigate the pyrolysis of different types of banana peel waste in order to develop a reliable platform for energy storage as well as waste management. The work comprises of designing a supercapacitor utilizing the as-synthesized AC as the electrode material with 2 M KOH as the electrolyte. The results showed that the electrode delivered a specific capacitance value of 227 F g -1 at 1 A g -1 current density and maintained a value of 155.5 F g -1 at a current density of 10 A g -1 when used in a three-electrode system. Moreover, the fabricated electrode showed excellent cyclic stability with capacitance retention of ∼97% for 5000 cycles. The AC material showed an outstanding rate performance in a symmetrical two-electrode full cell configuration with an operating potential window of 0–1 V using 2 M KOH electrolyte. The fabricated symmetric cell showed a maximum energy density of 7 Wh kg −1 at a power density of 250 W kg −1 . The banana peel derived AC exhibits capacitance behavior and thus have the capability of broadening the electrode materials horizon and also provide broad prospect in various specialized applications. Graphical Abstract: ga1 Highlights: Activated carbon was synthesized from banana peel waste using chemical activation process. The activated carbon electrodes showed specific capacitance as high as 227 Fg -1 at 1 Ag -1 . The electrode has achieved a high capacitance retention of ~ 97%. The fabricated symmetric device exhibits a maximum energy density of 7 Wh kg −1 at a power density of 250 W kg −1 . The porous surface of the particles is responsible for EDLC performance enhancement.